1991
DOI: 10.1142/s0217732391000075
|View full text |Cite
|
Sign up to set email alerts
|

The Β-Function IN TOPOLOGICAL SIGMA MODELS

Abstract: The one-loop β-function is computed for topological sigma models. By gauge fixing the topological shift symmetry in the delta-function gauge, we find that the theory is finite with vanishing β-function. A similar result is shown to hold for supersymmetric quantum mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 0 publications
0
92
0
Order By: Relevance
“…These operators {D + , D + µ , D + A } satisfy the following relations: 5) where Z commutes these operators…”
Section: N = Twisted Susy With Central Chargementioning
confidence: 99%
“…These operators {D + , D + µ , D + A } satisfy the following relations: 5) where Z commutes these operators…”
Section: N = Twisted Susy With Central Chargementioning
confidence: 99%
“…In [1]- [4], it was shown that a certain vector supersymmetry algebra was powerful enough to supply a foundation for both cohomological gauge and gravity theories; the gauge theories could be based on a theory of global vector supersymmetry, while local vector supersymmetry was the essential ingredient for gravity. Although a formulation of cohomological gauge theory was already known [5], an equally satisfactory treatment of gravity was elusive, for various attempts see [6]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed in [1] that the underlying algebra of cohomological gauge theory contained a global vector supersymmetry operator, in addition to the known BRST symmetry [5]. This led to an algebraic understanding of the descent equations de ning the observables, and indicated the generalization to a theory of cohomological gravity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations